The Strawberry letter : real talk, real advice, because bitterness isn't sexy - Strawberry, Shirley; LeFlore, Lyah Beth. (New York : One World/Ballantine Books, 2011)
'Listen up, ladies! Shirley Strawberry, co-host of the nationally syndicated Steve Harvey Morning Show, delivers more of the no-nonsense woman-to-woman straight talk her listeners have come to love. Shirley tells it like it is--from the heart. Whether the topic is cheating boyfriends, crazy mothers-in-law, job troubles, or money problems, Shirley's girlfriend-next-door honesty has made the Strawberry Letters segment of the show a huge hit. Now, in this uplifting motivational guide, she brings her vivacious, inspirational, and down-to-earth message to women everywhere: Get up, get out, and be the best you can be! As a single parent and a woman willing to let Mr. Right find her, Shirley's been there and done that--and she's got hard-won lessons to share. In this call to action to help women look at their lives with a candid eye, she tackles the issues her fans want to hear about: Love and Relationships: the highs and lows of dating, marriage, and breakups. Family: the challenges of being a great mom. Sisterhood: ways to get (and give) the support you need to stay sane. Self: tips for overcoming low self-esteem and depression, and finding balance, faith, and acceptance Full of motivating'Strawberry Tips,' personal stories that provide welcome advice on the run, and helpful suggestions for drama-stuck girlfriends, this book offers a simple message of strength: a challenge to love yourself and your life!'--
Keywords: Interpersonal relations; Women -- Conduct of life; Man-woman relationships; SELF-HELP / General